Principles of measurement and instrumentation - Morris, Alan S. 1948- (Prentice Hall, 1993)
This text presents the subject of instrumentation and its use within measurement systems as an integrated and coherent subject. This edition has been thoroughly revised and expanded with new material and five new chapters. Features of this edition are: an integrated treatment of systematic and random errors, statistical data analysis and calibration procedures; inclusion of important recent developments, such as the use of fibre optics and instrumentation networks; an overview of measuring instruments and transducers; and a number of worked examples.